Analisis Perubahan Eksternal dalam Pengembangan Kawasan Wisata Bahari Kepulauan Sapeken Madura dengan Menggunakan Pendekatan Pemasaran Wilayah - Muchammad Nurif; Endang Sulastri (Jurnal Sosial Humaniora, 2025)
To market the potential of marine and tourism, especially marine tourism required an appropriate marketing model for an optimal result. Given the area of Sapeken Island adjacent to P.Bali which is the icon of Indonesian tourism, the prospects of tourism development, including marine tourism, is very good that is by attracting tourists both domestic tourists and foreign tourists to continue the tour from P.Bali to the Sapeken Islands.. The rebuilding of Trunojoyo airport in Sumenep regency to be operated commercially will facilitate tourist access to visit Sumenep regency and then to Sapeken Islands because in Sapeken sub-district is P.Saor Desa Sapeken, P.Pagerungan Besar (former Pertamina). By knowing the potential in Sapeken region, including the potential of marine tourism spread across several small islands, and the role of tourism sector in moving the economy of a region, it is necessary to find a strategy or model to market these potentials in the package.